Long-term stability and reproducibility of Coagu Chek test strips - van den Besselaar, Anton M. H. P.; Hoekstra, Martha M. C. L. (Thrombosis and Haemostasis, 2005)
Whole-blood point-of-care testing prothrombin time monitors are being used on an increasing scale for the monitoring of oral anticoagulant therapy. These monitors are used with disposable test strips containing tissue factor reagent. The purpose of the present study was to assess the stability of different Coagu-Chek-S strip lots for a period of one year. Ten strip lots introduced successively in the Netherlands were obtained from the manufacturer's representative and stored at 4–8°C. Six deep-frozen pooled plasmas were analyzed for the prothrombin time and INR with the strips at six or seven occasions spread over one year. The test plasmas were recalcified immediately before application to the Coagu Chek-S system. Regression analysis was performed on the clotting times obtained with each plasma. In the majority of cases (i.e. 95%), no significant change was observed at the 5% significance level. A significant change was observed in only 3 cases. In addition, a ranking statistic was used as test of a monotonic relationship in the two-way analysis of variance. The results of the ranking statistic were not significant for any strip lot, indicating that the test strips were stable under these storage conditions. The reproducibility of INR measured with the Coagu Chek-S was assessed. The mean within-run coefficient of variation (CV) of INR ranged from 2.58% to 3.36% (CV). The between-lot variation of the mean INR ranged from 3.2 to 4.5 % (CV). The over-all variation of single INR measurements, i.e. including between-lot and within-lot, ranged from 5.0 to 6.0 % (CV).
Keywords: Point-of-care testing; oral anticoagulant therapy; prothrombin time; INR; quality control